Measurement of Supply Chain Management Performance in the Wood Pellet Industry Using the SCOR Method Based on AHP, OMAX, and Traffic Light System - Putri, Jeanny Shekinah Karani; Pulansari, Farida (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Wood pellets are one of the renewable fuels that are environmentally friendly and have the advantage of lower emission values than fossil fuels, so the increasing use of renewable energy fuels today. PT Yale Woodpellet Indonesia is one of the industries engaged in the production of wood pellets. Due to the increasing demand, PT Yale Woodpellet Indonesia once did not reach the production target. The approach that can be used to fix this problem is the SCOR (Supply Chain Operation Reference) model combined with AHP (Analytic Hierarchy Process), OMAX (Objective Matrix) and Traffic Light System to support the research. Based on the results of observations, interviews and distributing questionnaires to the company, 12 performance indicators were selected which were adjusted to the company's conditions. The results showed that there are two KPIs (Key Performance Indicator) that have not reached the target, which are in the yellow category so that corrective action needs to be taken to improve the company's supply chain performance. The KPIs are Qualification Accuracy of Raw Material (Slc) and Number of Trouble Machines (M2a).